2017
DOI: 10.1186/s12886-017-0567-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the VSX1 gene in sporadic keratoconus patients from China

Abstract: BackgroundKeratoconus normally presents as a sporadic disease. Although different studies have found sequence variants of the visual system homeobox 1 (VSX1) gene associated with keratoconus in humans, no research has detected such variants in sporadic keratoconus patients from China. To investigate the possibility of VSX1 being a candidate susceptibility gene for Chinese patients with sporadic keratoconus, we performed sequence screening of this gene in such patients.MethodsWhole DNA was obtained from the leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…It has also been observed that there are six transcripts and five variants which encode a truncated protein, while two of them retain the DNA-binding domain [ 261 ]. The five exons of VSX1 encode a protein consisting of 365 amino acids with a homeobox DNA-binding domain, a ceh-10 domain, and a Chx10/VSX1 domain [ 166 , 249 , 262 ]. The mRNA from the VSX1 gene is detected in embryonic craniofacial tissue, in the inner layer of the retina, and in the cornea [ 249 , 257 , 258 ].…”
Section: The Vsx1 Genementioning
confidence: 99%
“…It has also been observed that there are six transcripts and five variants which encode a truncated protein, while two of them retain the DNA-binding domain [ 261 ]. The five exons of VSX1 encode a protein consisting of 365 amino acids with a homeobox DNA-binding domain, a ceh-10 domain, and a Chx10/VSX1 domain [ 166 , 249 , 262 ]. The mRNA from the VSX1 gene is detected in embryonic craniofacial tissue, in the inner layer of the retina, and in the cornea [ 249 , 257 , 258 ].…”
Section: The Vsx1 Genementioning
confidence: 99%
“…Based on such a huge population, the number of potential KC patients might be enormous in China. Articles have unveiled the relationship between KC associated genetic loci (VSX1, IL1A, IL1B, COL4A3 and COL4A4) and Chinese Han ethnicity [10][11][12] . However, epidemiological study of KC among Chinese population is kind of a blank, except a research from Singapore in which only 60.3% of their subjects were made up of Chinese in 2011 and a research that simply illustrated several clinical features of Chinese KC patients in 2005 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…KC is characterized by the thinning of the central cornea and change in corneal shape, thereby leading to myopia and irregular astigmatism. Although the majority of KC cases are sporadic, genes correlated with KC, including VSX1 , have been reported [1, 2]. Furthermore, it has been reported that approximately 6–10% of KC patients have a familial history of the disease [3, 4].…”
Section: Introductionmentioning
confidence: 99%